European Surgical Education and Training in Gynecologic Oncology: The impact of an Accredited Fellowship - Chiva, Luis M; Mínguez, Jose; Querleu, Denis; Cibula, David; Du Bois, Andreas (International journal of gynecological cancer, 2017)
OBJECTIVE: The aim of this study was to understand the current situation of surgical education and training in Europe among members of the European Society of Gynecological Oncology (ESGO) and its impact on the daily surgical practice of those that have completed an accredited fellowship in gynecologic oncology. METHODS: A questionnaire addressing topics of interest in surgical training was designed and sent to ESGO members with surgical experience in gynecologic oncology. The survey was completely confidentially and could be completed in less than 5 minutes. Responses from 349 members from 42 European countries were obtained, which was 38% of the potential target population. The respondents were divided into 2 groups depending on whether they had undergone an official accreditation process. RESULTS: Two thirds of respondents said they had received a good surgical education. However, accredited gynecologists felt that global surgical training was significantly better. Surgical self-confidence among accredited specialists was significantly higher regarding most surgical oncological procedures than it was among their peers without such accreditation. However, the rate of self-assurance in ultraradical operations, and bowel and urinary reconstruction was quite low in both groups. There was a general request for standardizing surgical education across the ESGO area. Respondents demanded further training in laparoscopy, ultraradical procedures, bowel and urinary reconstruction, and postoperative management of complications. Furthermore, they requested the creation of fellowship programs in places where they are not now accredited and the promotion of rotations and exchange in centers of excellence. Finally, respondents want supporting training in disadvantaged countries of the ESGO area. CONCLUSIONS: Specialists in gynecologic oncology that have obtained a formal accreditation received a significantly better surgical education than those that have not. The ESGO responders recognize that their society should lead the standardization of surgical training and promote ways of improving members' surgical skills.
Keywords: ženské pohlaví; Female; Evropa; Humans; lidé; gynekologie; chirurgická onkologie; Europe; Gynecology; Genital Neoplasms, Female; Surgical Oncology; nádory ženských pohlavních orgánů